The Development of Learning Activities Package Learning Management Design Project-Based Learning and STEM Education of Student Teachers at Surin Rajabhat University - Jantamuttuakarn, Urai; Wongtamart, Kamonrat; Disom, Neenara; Pradabsri, Pikun (Journal for Developing the Social and Community, 2023)
This research aims to develop a series of learning activities and, -a design for project-based learning management for, -STEM education, and also to evaluate the effectiveness this activity package. The sample size consisted of 20 student teachers form a group of primary and fifth - grade teachers. The research tools included the learning activities package and a cognitive test on learning management design both before and after using the activity set. This included 1) a learning activity set consisting of 7 topics in the manual and activity pack: (1) an introduction to project-based and STEM-based learning management; (2) unit/target design and selection of indicators; and (3) content writing. The importance of the unit and the selection of questions was based on (4) the design of activities in the project unit; (5) the design of STEM activities and engineering processes; (6) the composition of the unit and how to write the details for each component; (7) and written learning activities. Each story consists of time spent, purpose, method of activities, media and learning resources assessments and assessment tools, knowledge sheets, power points, and worksheets. 2) The effectiveness of the learning activity package was 0.65.